Leverage, Profitability and Firm Value: The Moderating Effect of Dividend Policy - Zulpajri, Fajar; Robbi, Muhammad; Rawi, Rawi (Research Collaboration Community (RCC), 2024)
Most investors experience failure in their investments. So it is necessary to provide positive or negative signals to investors to obtain more accurate information regarding the risks they will face and the percentage of profits they will obtain. If the company can provide positive signals to investors, it will create a sense of satisfaction and trust in the company so that the value of the company will increase. This research uses quantitative methods. This research aims to ascertain whether company value is influenced by leverage and profitability by introducing dividend policy as a moderating factor. The population used is the LQ45 Company listed on the BEI in 2018-2022. The Purposive Sampling Method is a sample selection method in this research using certain criteria. This research data analysis approach uses SPSS 25 software for moderation testing and multiple linear regression analysis. Based on the research findings, corporate value can be affected by profitability and leverage, and it can be generally moderated by dividend policy. Keywords: Leverage, Profitability, Dividend Policy, Firm Value